Western Women and Islam: Embracing and Negotiating Muslim Identity. (1st January 2014) - ,
Abstract : Today, women-related questions are considered to be one of the most controversial questions regarding Islam in Europe. The resurgent interest in Women, as well as the gender questions emanating, and spreading from the West is due to an increasing, more assertive and visible Muslim population, and the ensuing issues focusing on women such as the hijaab and niqaab (veil). As a corollary to this, gender issues are central in the discussions of conversion to Islam, whereby female conversion to Islam has become a focal point of Western efforts to understand Islam. This paper aims to provide an overall analysis of the phenomenon of the appeal, and embracing of Islam by Western women in the context of how they view the status given to them by Western society, the pull and push factors; their attempt to create a niche of identity, dignity and equity for Muslim women both within the discourse among Muslims on the role of women in Islam, as well as a space within the overall narrative of ''Islam in the West;'' all of this being despite the polemics centering on the rights of women where the portrayal of Islam is that of a patriarchal, sexist religion that subjugates and demeans women.